Legal analysis of the management of harvest residues in South-West Europe - Cazorla González, María José (Przegląd Prawa Rolnego, 2020)
The Waste Directive establishes the basic principles of waste management, but it does not regulate issues relating to crop residues that remain on the farm, which creates a legal vacuum at the level of European Union law. In this situation, Member States are obliged to respond to problems arising from certain types of production. The article presents the current situation in this area in south-western Europe, where, due to the seasonal nature of production, crop residues arise at certain times of year. As we know, the common agricultural policy promotes the sustainable development of agriculture in relation to production carried out on European territory, which is why, according to the author, it is necessary to introduce appropriate legal regulations. The proper use and management of these residues by farmers may contribute to the improvement of their income which is consistent with the principles of circular management as part of the valorisation of these harvest residues.